Analisis Konsep Monopoli dalam Ekonomi Mikro Islam dan Implikasinya terhadap Keadilan Pasar - Hasanatun Fitri; Artika Tri Septia; Reni Ria Armayani Hasibuan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Monopoly is a form of market structure characterized by sole control over certain goods or services. In conventional economics, monopoly is often considered as part of market dynamics that can be tolerated under certain conditions, such as natural monopoly. However, from an Islamic microeconomic perspective, monopoly is viewed more critically because it has the potential to cause injustice in the distribution of wealth and market access. This article aims to analyze the concept of monopoly in Islamic economics and examine its implications for market justice. This study uses a descriptive qualitative approach based on literature studies, with sources from classical Islamic literature, the Qur'an, hadith, and contemporary economic theory. The results of the analysis show that Islam forbids monopolistic practices that are detrimental to society, especially in the form of ihtikar or hoarding, and encourages healthy competition and market supervision (hisbah). Thus, the principle of market justice in Islam is not only normative, but has a strong ethical and practical basis to prevent economic domination by a handful of parties.